E-Banten sebagai Media Online Penjualan Banten di Bali (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Bali is an island that is very diverse in culture. One of the cultures that exist in Bali is a very unique means of carrying out Hindu ceremonies. The means of the ceremony itself, called Banten, is a medium for visualizing Hindu teachings and for conveying Sradha and Bhakti to Hyang Widhi's omnipotence. Now the Balinese people prefer to buy offerings for religious ceremonies. With the advent of the digitalization era, now everything can be done without meeting face to face, one of which is the field of e-commerce for buying and selling products online. Here the author is moved to create a website-based application, namely e-Banten using the waterfall method. e-Banten itself is a messaging application between Banten which is carried out via online orders. Keywords: Banten, Balinese Hindu community, Website, E-commerce, Waterfall.